2015
DOI: 10.1111/irel.12088
|View full text |Cite
|
Sign up to set email alerts
|

Formal, Justice‐Oriented Voice in the Nonunion Firm: Who Speaks Up and When?

Abstract: Employee willingness to exercise workplace voice has been the subject of much recent research. However, very different types of voice are observed within the workplace, with some forms of voice receiving limited scholarly attention. In particular, limited attention has been given to the determinants of formal, justice‐oriented voice within a nonunion context. Using a policy‐capturing design, we examine factors that affect decisions to use formal, justice‐oriented voice among 498 nonunion employees who had acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 91 publications
(167 reference statements)
0
7
0
Order By: Relevance
“…Those describing low levels of voice at low levels of POS may have perceived that workplace leaders would not be willing or available to listen (i.e. that their voice has low utility; Klaas and Ward, 2015), or may have been worried that their voice would result in retribution (i.e. quiescent silence; Pinder and Harlos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Those describing low levels of voice at low levels of POS may have perceived that workplace leaders would not be willing or available to listen (i.e. that their voice has low utility; Klaas and Ward, 2015), or may have been worried that their voice would result in retribution (i.e. quiescent silence; Pinder and Harlos, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, union‐focused (collective) voice would also follow different pathways. Thus, while our research agenda is broad in identifying voice pathways over a range of matters, this article segments our initial contribution through illustrative cases of grievance articulation providing us an opportunity to initially understand what motivates employees to correct a perceived injustice or mistreatment (Klaas and Ward 2015). We then contend that understanding pathways is equally important for other types of voice, such as pro‐social or collective voice related to work issues and concerns for workplace improvements, or as many voice articles use Hirschman’s (1970) suggestion, to escape an objectionable state of affairs.…”
Section: Towards a Theoretical Framework Of Voice Pathwaysmentioning
confidence: 99%
“…Delineating antecedents to pro‐social and justice voice, Klaas, Olsen‐Buchanan and Ward (2012) identified that the relationship one has with their supervisor, perceptions of psychological safety and managerial reactions to voice were related to both of these voice types. Confidence about being able to prove claims is also significantly related to employees’ motivations to engage in formal grievance voice (Klaas and Ward 2015).…”
Section: Towards a Theoretical Framework Of Voice Pathwaysmentioning
confidence: 99%
“…For example, research has found that a high level of trust in managers leads employees to communicate with the manager (Gao et al, 2011). In addition, the willingness to appeal to the senior manager or a third party to address perceived mistreatment was likely to relate to whether the employees perceived themselves as being immune from actions that might flow from negative managerial reactions (Klaas and Ward, 2015). An empirical research study conducted in Western Canada showed that a cooperative union–management climate was likely to increase the chances of grievances being resolved or partially resolved because when a union–management relationship was good, the grievances were usually examined in the spirit of cooperation and problem-solving (Dastmalchian and Ng, 1990).…”
Section: Theory and Hypothesesmentioning
confidence: 99%